India's External Debt - N. V. Galistcheva (MGIMO University Press, 2012)
The article deals with one of the most important characteristics of Indian economy – its external debt. The author analyses in detail the composition of Indian external debt as well as the government’s policy on its payment. The article also presents different indicators on external debt, which characterize the depth of the economic problem for India.